Evaluation of AMELX gene polymorphism regarding gender and caries risk - Gül Yıldız; R. Banu Ermiş (Gazi University, 2017)
Objective: AMELX is the gene encoding amelogenin, which is involved in biomineralization during tooth enamel development. The genetic variation of this protein contributes to structural alterations of the enamel that may cause mineral loss and increased caries risk. The aim of this study was to investigate whether single nucleotide polymorphism of AMELX located on the X chromosome led to greater number of women (XX chromosome set) in the high caries risk group. Materials and Method: Genomic DNA was extracted from the buccal mucosa of 77 adults with 'low caries risk group' (DMFT≤5) and 77 adults with 'high caries risk group' (DMFT≥14) aged 20-60 years. The allele and genotype frequencies of AMELX (+522, rs6639060) single nucleotide polymorphism (SNP) were genotyped with the PCR-RFLP method. The difference of allele and genotype frequencies of AMELXacross gender and risk groups was compared with the chi-square test. The level of significance was set at p<0.05. Results: There was no significant difference between the low and high caries risk groups in relation to gender (p>0.05). No significant difference was found regarding the distribution of AMELX (+522) gene polymorphism between the low and high caries risk groups (p>0.05). Differences between the two genders for allele (chi-square=10.006, p=0.002) and genotype (chi-square=8.189, p=0.017) frequencies of AMELX (+522) were statistically significant. The frequency of TT polymorphism was found to be 41.7% in women and 58.3% in men. The frequency of T allele was found to be 39.7 % in women and 60.3% in men. Conclusion: AMELX (+522, rs6639060) gene polymorphism was not associated with caries risk, and the number of polymorphic genotypes and alleles was lower in women than in men.